THE WITCHES IN SHAKEASPEARE’S MACBETH - Mochamad Nasrul Chotib; Nanang Endrayanto (Jurnal Humanitas)
Taking into account the existence of the witch characters in Macbeth, this study was performed to analyze the social function of the due characters. In so doing, the historical design was used to locate the play as it was socially and originally perceived by its contemporary audiences. The result shows that such characters serve both structurally and socially as well: structurally to justify the course of the hero disgracing fate and socially to maintain the idea of the necessary goodness